2017
DOI: 10.1016/j.ijfoodmicro.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial communities of donkey milk by high-throughput sequencing

Abstract: 27The interest in donkey milk (DM) is growing because of its functional properties and 28 nutritional value, especially for children with allergies and food intolerances. However, most 29 of the available reports of DM microbiota are based on culture-dependent methods to 30 investigate food safety issues and the presence of lactic acid bacteria (LAB). 31The aim of this study was to determine the composition of DM bacterial communities using a 32 high-throughput sequencing (HTS) approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 34 publications
5
31
0
Order By: Relevance
“…The prevalence of certain microbes could undoubtedly reflect the hygienic conditions of milk production. For example, the Pseudomonas genus has been consistently reported to be dominant microbes of raw milk (Sørhaug and Stepaniak, 1997;Quigley et al, 2013;Soto Del Rio et al, 2017). Our current data showed a high relative abundance of Pseudomonas (>34%) in samples XT2, XT5, and XT12.…”
Section: Discussionsupporting
confidence: 58%
“…The prevalence of certain microbes could undoubtedly reflect the hygienic conditions of milk production. For example, the Pseudomonas genus has been consistently reported to be dominant microbes of raw milk (Sørhaug and Stepaniak, 1997;Quigley et al, 2013;Soto Del Rio et al, 2017). Our current data showed a high relative abundance of Pseudomonas (>34%) in samples XT2, XT5, and XT12.…”
Section: Discussionsupporting
confidence: 58%
“…In a recent work, the bacterial composition of donkey milk from different farms was analysed by high-throughput sequencing, revealing the occurrence of the same phyla [16]. These authors found a higher concentration of Proteobacteria (more than 85%) and a lower composition in Bacteroidetes (less than 1%) in almost all samples [16], suggesting that the microbial milk composition could be strictly related to the different breeding conditions.…”
Section: Analysis Of Bacterial Diversitymentioning
confidence: 99%
“…However, few studies aimed to elucidate the composition of the microbiota of non-cow milk and the corresponding products [13]. To date, knowledge on the microbiota of donkey milk is limited to only a few studies, mainly addressed by culture-dependent tools [14,15] and, only recently, by a metagenomic approach [16].…”
Section: Introductionmentioning
confidence: 99%
“…The milk microbiota has been mostly investigated in women (Hunt et al, 2011;Jost et al, 2013;Fitzstevens et al, 2016) and in cows (Oikonomou et al, 2014;Addis et al, 2016;Falentin et al, 2016); some studies were also conducted in other mammals such as goats, sheep, donkeys, buffalo, water deer, reindeer, or mice (Quigley et al, 2013;McInnis et al, 2015;Treven et al, 2015;Catozzi et al, 2017;Li et al, 2017;Soto Del Rio et al, 2017; Supplementary Table S1). Most studies on milk microbiota have investigated milk collected by manual expression, generally following thorough cleaning of nipples or teats (Oikonomou et al, 2012;Jost et al, 2013;Boix-Amoròs et al, 2016) (Figure 1).…”
Section: Milk Microbiota: Current Studies and Limitsmentioning
confidence: 99%
“…Human milk microbiota diversity has also been supported by culture-dependent approaches, which beyond the dominant genera Staphylococcus, Streptococcus, and Propionibacterium allowed the isolation of members of Bifidobacterium, Rothia, Enterococcus, Lactobacillus, or even obligate anaerobes such as Veillonella (Perez et al, 2007;Jost et al, 2013). Milk microbiota has also been investigated in other animals, including donkey, goat, sheep, water deer, reindeer, and water buffalo, although the number of studies is limited compared to that of studies of human and cow milk ( Supplementary Table S1), showing some overlap with human and cow milk microbiota (Figure 2; Castro et al, 2011;McInnis et al, 2015;Catozzi et al, 2017;Li et al, 2017;Soto Del Rio et al, 2017;Esteban-Blanco et al, 2019). Nevertheless, significant differences have been reported in the milk bacterial communities of different ruminants, such as water deer, reindeer, and goat, suggesting host microbial adaptation, although influence of environment and herd management should not be excluded (Li et al, 2017).…”
Section: A Core Milk Microbiota Universally Shared Between Hosts?mentioning
confidence: 99%